Enhancing performance of slotted ALOHA protocol for IoT covered by constellation low-earth orbit satellites - Chabou, Zakaria; Addaim, Adnane; Ait Madi, Abdessalam (Bulletin of Electrical Engineering and Informatics, 2024)
Recently, constellation of satellites has drawn a lot of interest from academia and industry as potential solution for extensive coverage of wide range of internet of things (IoT). In this work, IoT devices was assumed to be covered by constellation of low-earth orbit (LEO) satellites where the medium access control (MAC) technique called slotted ALOHA is employed. In this article, we use a constellation of satellites to reduce the collision domain and enhancing performance in order to obtain maximum results. We have carried out some modeling and simulations to optimize the number of satellites with different erasure probabilities with respect to IoT devices in order to enhance throughput and stability of slotted ALOHA protocol using the network simulator 2 (NS2). The numerical results have shown an improvement in terms of throughput and stability. And the simulation of the same system using NS2 is conducted and shows a good correlation with the theoretical study. Where the throughput reached 0.82% instead of 0.52%. Our findings offer proof that this method helps to use large number of IoT, and reduce collisions compared to conventional slotted ALOHA.